Cultural Resources and Maternal Health in Mali - Clemmons, Lydia (World Bank, Washington, DC, 2012)
In spite of the cultural, traditional taboo on the subject of pregnancy in most African households, the success of the Africare's Child Survival Project in Mali, documents the increased communication, and behavior changes in health seeking during pregnancy. Africare is a US-based private, voluntary organization, working in community development, and through its efforts, constructed a maternity ward in the country, supported by government health professionals. The note describes the research work underwent by Africare to identify both resources, and obstacles related to to improved maternal health, and care-seeking. Findings revealed that both women, and men were well aware of the risks associated with pregnancy, enhanced by cultural traits which places a strong value on supportive husbands during pregnancy. However, one of the most striking cultural obstacles to women's maternal health care, was the absence of discussions on the subject, due entirely to the taboo issue about sexual relations, and pregnancy. Following a pilot maternal health campaign - based on cultural, traditional channels in identifying maternal, and pregnancy issues - the impact of the project was evaluated, demonstrating those channels used to communicate, can be effectively innovated to adapt them to modern needs.